PENGARUH PENGETAHUAN AKUNTANSI DAN PENGALAMAN USAHA TERHADAP PENGGUNAAN INFORMASI AKUNTANSI PADA PELAKU UMKM - Purwaningrum, Desyani; Fandil, Fandil; Bayu Pertiwi, Dyah Nurul (Sekolah Tinggi Ilmu Ekonomi Semarang, 2025)
This study aims to analyze the effect of accounting knowledge and business experience on the use of accounting information among Micro, Small, and Medium Enterprises (MSMEs) in Cepogo District, Boyolali Regency. The background of this research is based on the low awareness of MSME actors in utilizing accounting information as a basis for business decision-making. Accounting knowledge and business experience are assumed to be the main factors influencing the limited use of accounting information among MSME owners. This research employs a quantitative approach with a causal-comparative design. The population consists of 150 MSME units in Cepogo District, with a total sample of 70 respondents selected using simple random sampling. Data were collected through questionnaires and analyzed using validity and reliability tests, classical assumption tests, multiple linear regression, t-test, F-test, and the coefficient of determination (R²) with the assistance of SPSS software. The results indicate that accounting knowledge has no significant effect on the use of accounting information among MSME actors in Cepogo District, suggesting that the level of accounting understanding does not significantly determine their application of accounting information. Conversely, business experience has a positive and significant effect on the use of accounting information, meaning that the longer entrepreneurs engage in business activities, the better they are in utilizing accounting information to support decision-making processes. The coefficient of determination (Adjusted R²) value of 0.621 shows that accounting knowledge and business experience explain 62.1% of the variation in the use of accounting information, while the remaining 37.9% is influenced by other factors not examined in this study. This study is expected to provide insights and references for MSME actors and the Department of Cooperatives and MSMEs of Boyolali Regency in developing financial management capabilities through training and mentoring programs in accounting, so that accounting information can be optimally used to improve business decision-making.